`1/2 + 5/4 - 7/7 + 3/4 - (1/2)^0`
`= 1/2 + 5/4 - 1 + 3/4 - 1`
`= 1/2 + (5/4+3/4)-(1+1)`
`= 1/2 + 2 - 2`
`=1/2+0`
`= 1/2`
`3/4 . (-27) - 3/4 . 73`
`= (-3/4) . 27-3/4 . 73`
`= (-3/4) . (27+73)`
`=(-3/4).100`
`= -75`
\(\dfrac{1}{2}+\dfrac{5}{4}-\dfrac{7}{7}+\dfrac{3}{4}-\left(\dfrac{1}{2}\right)^0\)
\(=\dfrac{1}{2}+\dfrac{5}{4}-1+\dfrac{3}{4}-1\)
\(=\dfrac{1}{2}+\left(\dfrac{5}{4}+\dfrac{3}{4}\right)-\left(1+1\right)\)
\(=\dfrac{1}{2}+\dfrac{8}{4}-2\)
\(=\dfrac{1}{2}+2-2\)
\(=\dfrac{1}{2}+\left(2-2\right)\)
\(=\dfrac{1}{2}\)
\(----------\)
\(\dfrac{3}{4}.\left(-27\right)-\dfrac{3}{4}.73\)
\(=\dfrac{3}{4}.\left[\left(-27\right)-73\right]\)
\(=\dfrac{3}{4}.\left(-100\right)\)
\(=-75\)